Consumer's perception of green marketing strategies. - Sheena Tomar. (2012)
This study aims to investigate consumer’s perception of the various green marketing strategies adopted by companies and their perception of the ecological image of the company. The green marketing strategies identified are green innovation, greening and green alliance. This quantitative study uses a deductive research approach to test the relationship between the variables. Using self-administered online surveys, our data collection was done through quota sampling. A total of 386 respondents were surveyed of which responses by 362 were used as they were ensured to be reliable and valid.